RISK-BASED AUDIT IMPLEMENTATION AND PROFESSIONAL SKEPTICISM ON FRAUD DETECTION FOR LOCAL GOVERNMENT FINANCIAL REPORTS - Deasy Aseanty; Arif Zulkarnain (Program Studi Magister Manajemen, 2023)
This analysis aims to investigate the effect of Risk-Based Audit Implementation and Professional Skepticism on Fraud Detection. The object of this research is 40 out of 88 examiners at the Audit Board of Republic Indonesia (BPK) Representative of Lampung Province who have been certified as examiners. The sample used in this study was a purposive sampling method, namely data collection from predetermined respondents. The research approach utilized in this research is a quantitative approach using multiple linear regression analysis with IBM SPSS Version 28.0 software as the analysis tool. The findings revealed that the Risk-Based Audit Implementation variable had a substantial positive effect on the Fraud Detection variable, Professional Skepticism had a significant positive effect on Fraud Detection, Risk-Based Audit Implementation, and Professional Skepticism had a significant positive effect simultaneously on Fraud Detection.